MODELING RHEOLOGICAL PROPERTIES OF SOME MOLASSES-TAHIN BLENDS - MOHAMMED, DLSHAD ABDALLA MOHAMMED (Fırat Üniveristesi, 2018)
Bu çalışmanın amacı deneysel verilere uyan bir model geliştirmek için farklı konsantrasyon (% 20–55) ve sıcaklıklarda (25–60 ?C) hurma, dut, üzüm ve keçiboynuzu pekmezleri-tahin gibi bazı pekmez-tahin karışımlarının döner viskozimetre (Brookfield) ile reolojik özelliklerinin belirlenmesidir. Kayma geriliminin fonksiyonu olarak her karışımın viskozitesini elde etmek için bu örnekler artan bir şekilde 5 farklı dönme hızında kayma gerilimine tabi tutuldu. Kayma gerilimleriyle (2.5–30 s-1) karışımların viskozitelerindeki değişim, çalışılan pekmez-tahin karışımlarının bütün sıcaklıklarda Newtonien olmayan kayma incelmeli sıvılar olduğunu gösterdi. Kayma gerilimlerine karşı görünür viskozitenin deneysel verileri üs kanunu modeli ile başarılı bir şekilde tanımlandı. Çalışılan karışımların akış davranışı indeksi (n) ve kıvamlılık katsayısı (K) gibi model parametreleri sırasıyla; hurma pekmezi-tahin karışımı için 0.522 ile 0.641 ve 4365.1 ile 10013 mPa.sn, dut pekmezi-tahin karışımı için 0.659 ile 0.699 ve 4461.1 ile 10207 mPa.sn, üzüm pekmezi-tahin karışımı için 0.331 ile 0.62 ve 966.88 ile 4218.2 mPa.sn ve keçiboynuzu pekmezi-tahin karışımı için 0.444 ile 0.599 ve 3194.4 ile 17480 mPa.sn aralıklarında bulundu. Karışımların görünür viskoziteleri ve kıvamlılık katsayıları pekmez konsantrasyonlarının artmasıyla ve sıcaklığın azalmasıyla arttığı gözlendi. Kıvamlılık katsayılarının sıcaklık duyarlılığı Arrhenius tipi eşitlik kullanılarak incelendi. Çalışılan karışımların aktivasyon enerjisi (Ea); hurma pekmezi-tahin karışımı için 4378.15 ile 9499 J/mol, dut pekmezi-tahin karışımı için 7514 ile 13216.7 J/mol, üzüm pekmezi-tahin karışımı için 4341 ile 17378.08 J/mol ve keçiboynuzu pekmezi-tahin karışımı için 6779.04 ile 13444.5 J/mol arasında bulundu. Her bir karışım için derişim ile kıvamlılık katsayısı arasındaki ilişki hem üstel hem de üs fonksiyonları ile tanımlandı. Ea'nın hurma, üzüm ve keçiboynuzu pekmezlerinin derişimleriyle değişiminin açıklanmasında üstel fonksiyonun daha üstün olduğu bulunurken, Ea'nın dut pekmezi derişimi ile değişimin açıklanmasında üs fonksiyonun daha iyi olduğu bulundu. Görünür viskozite üzerinde sıcaklık, bazı pekmez derişimleri ve kayma geriliminin birleşik etkisini yüksek tutarlılıkla tanımlama için bir matematiksel model belirlendi.

The aim of this study is to determine the rheological properties of some molasses-tahin blends such as date syrup-tahin, mulberry molasses-tahin, grape molasses-tahin and carob syrup-tahin (sesame paste) blends at the different ratios (20 -55 %) and different temperatures (25- 60 °C) by using a rotary viscometer (Brookfield) to develop models appropriate to the experimental data. In order to obtain the viscosities of each blend as a function of the shear strain, those samples were sheared with five different rotational speeds at an increasing order. The variation of viscosity of those blends with the strain rates (2.5-30 s-1) showed that all considered ratios of the molasses-tahin blends were non-Newtonian shear thinning fluids at all temperatures. The experimental data of apparent viscosity versus shear rate were successfully described with the Power-law model. The model parameters such as the flow behavior index (n) and the consistency coefficient (K) of the considered blends were respectively found to be ranged from 0.522 to 0.641 and from 4365.1 to 10013 mPa.sn for the date molasses- sesame paste blends; from 0.659 to 0.699 and from 4461.1 to 10207 mPa.sn for mulberry molasses- sesame paste blends; from 0.331 to 0.62 and from 966.88 to 4218.2 mPa.sn for grape molasses- sesame paste blends; from 0.444 to 0.599 and from 3194.4 to 17480 mPa.sn for the carob molasses- sesame paste blends. It was observed that apparent viscosities and consistency coefficients of blends increased with increasing molasses concentration and decreasing temperature. Temperature sensitivity of the consistency index (K) was examined using an Arrhenius-type equation. Activation energies (Ea) of the considered blends were found to be ranged from 9499 to 4378.15 J/mol for the blends of date molasses-sesame paste; from 13216.69 to 7514 J/mol for the blends of mulberry molasses-sesame paste; from 17378.08 to 4340.98 J/mol for the blends of grape molasses-sesame paste; from 13444.5 to 6779.04 J/mol for the blends of carob molasses-sesame paste. The relationship between concentration and consistency coefficient for each blend was described with both the exponential and power functions. While the exponential function was found to be superior in explaining the variation of Ea with concentrations of date, grape and carob molasses, power function was found to be superior in explaining the variation of Ea with concentration of mulberry molasses. A mathematical model was determined to describe the combined impact of temperature, concentrations of the molasses and shear rate on apparent viscosity with high consistency.
Bazı pekmez-tahin karışımlarının reolojik özelliklerinin modellenmesi
Keywords: Kimya Mühendisliği